FRAMING DAN REPRESENTASI SIMBOL ABSTRAK (STUDI KASUS SAMPUL NOVEL SUPERNOVA) - Ria Fathya Luqman (ARTic, 2018)
At year 2012-2014, Bentang Pustaka Publisher, republished 5 Supernova novels by Dee Lestari which the cover was designed by Fahmi Ilmansyah with displays visual abstract symbol on the novels cover. This research discusses 5 Supernova cover published by Bentang Pustaka publisher. The novels is Supernova series 1 Kesatria, Putri, dan Bintang Jatuh, series 2 Akar, series 3 Petir, series 4 Partikel, and series 5 Gelombang. The methodology of study uses qualitative method that approach framing analysis that is a discussion of selection an aspect of an issue or reality to make it look more attractive. The result shows that the designer has been done framing 5 cover of Supernova novel Bentang Pustaka publisher with visualization of abstract symbol on the cover that is Supernova series 1, 3, and 5 cover selecting climax of the story, while series 2 and 4 cover selecting conflict of the story. As well as meaning of the abstract symbols and reality on the novel that has been selected, except on the series 5 cover. From this research, it can be concluded that designer have framed section are important in the novels and external factor of the novels content, as a long age of novels, segmentation, and effort to build a visual identity of it also effect to designer is framing on showing visual abstract symbol on the cover of Supernova novels.